Life Stages, Source Of Infestation And Control Of Rhinoceros Beetle Oryctes Rhinoceros (LINN) (Coleoptera: Scarabaeidae) In A Newly Replanted Oil Palm Plantation - Mamat, Wan Zaki Wan (2008)
The life stage of Oryctes rhinoceros was investigated in empty fruit bunches (EFBs) in a newly replanted area in FELDA Lepar Utara 05 Plantation, Bandar Jengka, Pahang. Three stages instar larvae (instar 1-3), prepupa and pupa were found in empty fruit bunches. However no egg was found during the study period. The larvae and pupae were continuously encountered in the EFB during 20 weeks of study.